Strategi Perpustakaan Dalam Mendukung Pembelajaran Secara Daring di Universitas Islam Negeri Raden Intan Lampung - Eni Amaliah; Rahmat Iqbal; Nadya Amalia Sholeha (Pustabiblia: Journal of Library and Information Science, 2022)
Circular No.36962/MPK.A/HK/2020 it was decided that online learning and working from home are for breaking the chain of the spread of covid19. The application of the online teaching and learning system is a means of proving the professional competence of librarians as a link of information between information sources and information users. The library law number 43 of 2007 states that a librarian is someone who has a competence. Based on several problems that exist in the online learning system in universities, especially at the Raden Intan State Islamic University Lampung (UIN-RIL), this paper raises a problem formulation, namely How Library Strategies Support Online Learning at Raden Intan State Islamic University Lampung. The method used in this research is qualitative with qualitative descriptive type. This study also reveals attitudes, events, relationships and views that occur in a scope of respondents. This study places more emphasis on the results. This study uses observation and interviews to strengthen the research analysis. Discussion of Library Service Transformation consists of Online Catalog, Circulation thru Service and Institutional Repository, Digital Promotion Information Communication and Mobile Library. Success in learning during a pandemic cannot be separated from the role of libraries and librarians in preparing strategically in providing library collection information or alternative sources of information.